Support from Superiors and Employee Turnover at a Manufacturing Company in Poland - Stolarska-Szeląg, Elżbieta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The aim of this paper was to analyse the impact of supervisor support, including the provision of appropriate induction training, on employees’ decisions to leave their jobs at a Polish manufacturing company. It also undertook to show how socio-economic characteristics influence the reasons for leaving a job. Research Design & Methods: The data was collected from people working in hazardous conditions at a manufacturing company. The company has been operating in Poland since 2016 and operates in the area of section C – industrial processing, division 10 – production of foodstuffs. 89 questionnaires were analysed. Data were collected over a period of 2.5 years. The following variables were controlled for: gender, length of service with the company, total length of service, supervisor support and provision of induction training. Subsequently, 14 reasons for leaving a job were identified and compared against the variables. The article used the chi-square statistical test and Cramér’s V test. Findings: Overwork and stress, as well as the need for change, were the most common reasons employees gave for leaving. The survey showed that the vast majority of respondents had received adequate induction training. Those who had not undergone adequate onboarding often left because they felt they had been undervalued, believed employees were treated unfairly, perceived a poor team atmosphere and/or had poor relations with their manager. No confirmation was found that turnover was a consequence of inadequate onboarding. The article examined the relationship between the lack of support from a supervisor and the reasons for leaving a job. It has been shown that people who did not receive support cite unequal treatment of employees as a reason for resigning from work. However, men leave work more often than women due to a feeling of being undervalued and lack of promotion opportunities. No correlation was found between gender and other reasons for leaving. Implications / Recommendations: Supervisor support can go a long way towards reducing employee stress and lowering turnover levels. Leaders actively supporting their employees can help them increase their sense of belonging and commitment to the organisation. Adapting motivation and development strategies to the specific needs of different groups of employees can help reduce turnover. Contribution: The issue of employee turnover has attracted the attention of researchers and human resource management practitioners in companies throughout the world. Despite this, there remains a gap in the Polish literature that would indicate the relationship between supervisor support and turnover intention in manufacturing companies. This study is an important prelude to further research on Poland and in manufacturing enterprises that are struggling with high levels of employee turnover. The article makes a significant contribution to the literature by providing valuable new data that can be applied to management practice in Polish manufacturing companies.